Perceptions of selected Malaysian information systems practitioners towards software prototyping: an exploratory study - Selamat, Mohd Hasan; Rahim, Md. Mahbubur; Mohamad Noor, Noor Maizura (Faculty of Computer Science and Information Technology, University of Malaya, 1996)
Studies the perceptions of the Malaysian IS practitioners about the use, applicability, problems, and benefits of prototyping approach in the development of software systems. This was accomplished by undertaking an exploratory survey among selected information systems practitioners. The results indicate that the adoption of prototyping approach is relatively a new concept to the Malaysian practitioners. It was found that prototyping models are not generally thrown away, and prototyping in third generation languages is common. Prototyping approach was further applied to develop a wide variety of applications ranging from real time to traditional business systems. Some of these findings are contrary to the existing literature on prototyping. Hence, despite the survey's restriction to small sample, the findings are important to information systems practitioners and academics.